2012
DOI: 10.1111/j.1753-4887.2012.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Limbic system pathologies associated with deficiencies and excesses of the trace elements iron, zinc, copper, and selenium

Abstract: Deficiencies of nutrients such as amino acids, vitamins, lipids, and trace elements during gestation and early infanthood have strong deleterious effects on the development of the limbic system; these effects may be irreversible, even when adequate supplementation is provided at later developmental stages. Recent advances in the neurochemistry of biometals are increasingly establishing the roles of the trace elements iron, copper, zinc, and selenium in a variety of cell functions and are providing insight into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 139 publications
(255 reference statements)
1
17
0
Order By: Relevance
“…In present study, we have observed that TPEN, a Zn 2+ chelator significantly attenuates the neurological deficit and brain infarction area in acute ischemic rat brains. The results were in good agreement with those recently reported by Zhao et al [39] It has been determined that, during neurotransmission in glutamatergic neurons, Zn 2+ and glutamate are co-released into the synaptic cleft [14]. It is also recognized that Zn 2+ influx from the extracellular space and its mobilization from intracellular pools such as mitochondria, cytosolic Zn 2+ binding proteins, and lysosomes lead to neuronal damage because of hypoxia/ischemia [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 90%
“…In present study, we have observed that TPEN, a Zn 2+ chelator significantly attenuates the neurological deficit and brain infarction area in acute ischemic rat brains. The results were in good agreement with those recently reported by Zhao et al [39] It has been determined that, during neurotransmission in glutamatergic neurons, Zn 2+ and glutamate are co-released into the synaptic cleft [14]. It is also recognized that Zn 2+ influx from the extracellular space and its mobilization from intracellular pools such as mitochondria, cytosolic Zn 2+ binding proteins, and lysosomes lead to neuronal damage because of hypoxia/ischemia [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 90%
“…There is evidence of lipid peroxidation in the substantia nigra induced by high levels of trace elements such as ferrous iron which can exacerbate cell damage in PD [ 146 , 148 ]. Studies have also shown that other trace elements such as manganese, selenium, copper, aluminum or zinc also play a role in neurodegeneration [ 149 , 150 ]. Their abnormal metabolism sometimes results in pathological conditions including depression and PD [ 149 , 150 ].…”
Section: Oxidative Stress Neuroinflammation and Parkinson’s Disease mentioning
confidence: 99%
“…copper (Cu) and iron (Fe). These metals are implicated in neurodegenerative pathology, including that of AD [29,89,90]. Indeed, some authors have ascribed the neuroprotective properties of SELENOP to its metal-binding properties.…”
Section: Biochemistry and Functions Of Selenopmentioning
confidence: 99%
“…However, since Aβ is presumably much more abundant in the AD brain than SELENOP, the most important effect might be the binding of Se such that it is unavailable for normal incorporation into selenoproteins. Since Cu is found relatively abundantly in Aβ [79] and Cu 2+ binds very strongly to Sec residues, [89], a ternary complex between Aβ, Cu 2+ , and SELENOP might be a plausible candidate for the co-localization with Aβ in AD brains. In particular, in mice neuroblastoma N2A cells Cu + /Cu 2+ promotes aggregation of tau and increases its cytotoxicity, compared to tau alone [104].…”
Section: Selenop Interaction With Bioactive Components Involved Inmentioning
confidence: 99%